Chronic bilateral bundle-branch block. Long-term observations in ambulatory patients. Issue 2 (February 1977) - Lister, J W; Kline, R S; Lesser, M E
Abstract : During a period of 28 months, all patients (79) who presented with bilateral bundle-branch block were selected for study from a private practice outpatient population. They were followed prospectively from the date of entry into the study and their charts were reviewed retrospectively. The average age of the participants was 73-3 years and they were observed clinically for a cumulative period of 4237 months (353-08 years). A high incidence of severe heart disease and death was noted among the study group. Twenty-four (30-3%) had a New York Heart Association functional classification of 3 or 4. Eight (10-1%) died. Only one patient died suddenly and he had had a stable electrocardiographic pattern of bilateral bundle-branch block for a period of 118 months (9 years 10 months). Seven patients required permanent pacemakers. In 6 instances death resulted from pump failure; in one it was the result of lung cancer. In none of these 7 individuals did rhythm disturbances contribute to death. In most cases vertigo was not of cardiac origin (88-2%). Eight patients had 11 major surgical procedures with no significant cardiac sequelae. Our observations suggest that elderly patients with chronic bilateral bundle-branch block should be managed conservatively. The prognosis in these patients appears primarily to be related to the degree of myocardial disease rather than to the conduction disorder.